2016
DOI: 10.1057/s41294-016-0014-0
|View full text |Cite
|
Sign up to set email alerts
|

The Middle-Income Trap: Definitions, Theories and Countries Concerned—A Literature Survey

Abstract: Abstract. In recent years, a growing body of economic literature has focused on the phenomenon of the so-called middle-income trap (MIT). The term usually refers to countries that have experienced rapid growth and thus quickly reached middle-income status, but then failed to overcome that income range to further catch up to the developed countries. This paper surveys the MIT literature. It begins by laying out different approaches to defining the MIT (with a focus on the distinction between absolute and relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
10

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(41 citation statements)
references
References 29 publications
1
26
0
10
Order By: Relevance
“…As mentioned in the previous part, among these three conditions, especially the third condition has received criticism due to its high threshold value in the literature (Paus, 2014;Fryer and Cattaneo, 2014;Glawe and Wagner, 2016;Andrianjaka and Rougier, 2017). Due to the third condition, several developed countries such as Australia, Japan and the USA are included in the analysis, whereas many developing countries are left out.…”
Section: Methodsmentioning
confidence: 99%
“…As mentioned in the previous part, among these three conditions, especially the third condition has received criticism due to its high threshold value in the literature (Paus, 2014;Fryer and Cattaneo, 2014;Glawe and Wagner, 2016;Andrianjaka and Rougier, 2017). Due to the third condition, several developed countries such as Australia, Japan and the USA are included in the analysis, whereas many developing countries are left out.…”
Section: Methodsmentioning
confidence: 99%
“…They defined growth acceleration as an increase in per capita income growth of 2 percentage points, conditional that it lasted for 8 years and the post-acceleration growth has to be at least 3.5 percent per year. 9 SeeGlawe and Wagner (2016) for a review of previous studies which used either absolute or relative approach in identifying middle-income countries.…”
mentioning
confidence: 99%
“…By examining the experiences of 80 countries, Yiping, Qin, and Xun (2014) suggested that, for the middle-income group, repressive policies on credit, bank entry, securities market, and the capital account significantly hinder economic growth. Glawe and Wagner (2016) argue that, except for the scenarios based on the World Bank (2013) study and some of Eichengreen, Park, and Shin (2012; scenarios which are based on borderline cases, most of the implied scenarios showed that the PRC is not yet at the MIT. The majority of their scenarios indicated that the PRC will soon enter into the middle-income country status, but not trapped in an MIT.…”
Section: Determinants Of Total Factor Productivity Growthmentioning
confidence: 99%